Recurrent Puerperal Uterine Inversion - Gurung, Monica; Baral, Gehanath (Nepal Journal of Obstetrics and Gynaecology, 2021)
Uterine inversion is rare and life threatening obstetric complication. This is a case of recurrent uterine inversion managed successfully with Johnson’s Maneuver followed by condom tamponade placement.